2016
DOI: 10.3390/su8060525
|View full text |Cite
|
Sign up to set email alerts
|

BIM and Sustainability Education: Incorporating Instructional Needs into Curriculum Planning in CEM Programs Accredited by ACCE

Abstract: Abstract:Higher education ought to support the identification of training needs for industrial building information modelling (BIM) curriculum development and sustainability education in the fields of civil engineering and management (CEM). This paper proposes a framework based on a four-phase step-by-step quality function deployment (QFD) application for CEM curriculum planning and quality management. The framework attempts to respond to requests collected from 17 professionals and professors in order to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 56 publications
(93 reference statements)
2
29
0
1
Order By: Relevance
“…Other researchers [23,24,73,74] recommend that the local government stimulate the transformation of construction enterprises and encourage these businesses to focus on implementing innovative business models such as service-driven engineering, procurement, construction, and partnering. In Table 8, the results from the entropy method are more consistent with still other research [34,50,52,55,75]. Questions such as "How significant is the attention given to propagating the lessons learned from successful projects in your company?"…”
Section: Discussionsupporting
confidence: 78%
“…Other researchers [23,24,73,74] recommend that the local government stimulate the transformation of construction enterprises and encourage these businesses to focus on implementing innovative business models such as service-driven engineering, procurement, construction, and partnering. In Table 8, the results from the entropy method are more consistent with still other research [34,50,52,55,75]. Questions such as "How significant is the attention given to propagating the lessons learned from successful projects in your company?"…”
Section: Discussionsupporting
confidence: 78%
“…In this research, we extend the growth management model into the innovation field of the construction industry with two comparative methods, i.e., average method and entropy method, to verify the original method and test the framework [17,18]. It is confirmed that, as a generic framework of growth management [16], the proposed model is valuable for analyzing the growth position of management policies of the construction industry.…”
Section: Introductionmentioning
confidence: 66%
“…This research utilized the following mixed method [17,18]: (a) average score method as the original validation method in growth management model; (b) entropy method as the proposed alternative method to comparatively analysis the growth management position; and (c) major impact index formula to target the top influence factor in the sustainable development of construction industrialization process. The calculation process is shown as follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, these changes in the historical habits of the current industry require actors that have an educational and training background to understand that the culture of virtual working space collaboration in the sense of time and location. Such cultural education cannot be achieved through fragmented seminars but through programs of undergraduate degrees with marketing learning outcomes (Zhang et al, 2016).…”
Section: Recommendationsmentioning
confidence: 99%